INCREASING THE STUDENT’S VOCABULARY MASTERY THROUGH HOW SPECIAL AM I GAME OF THE TENTH GRADE SMK NEGERI 1 GUNUNGSITOLI IN 2022/2023 - Waruwu, Fitdarlin; Daeli, Hidayati; Telaumbanua, Yasminar Amaerita; Efori Telaumbanua, Kristof Martin (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
Vocabulary is the most important component of the overall communicative competence that enables students to convey information, ideas or notions to others in such written and oral form. Vocabulary mastery is the ability to use the words in conducting the communication and understanding the meaning of the words or phrases in English. The research was conducted by using Classroom Action Research (CAR) design. This research was applied into two cycles. Each cycle consisted of planning, action, observation, and reflection. In the second meeting of cycle II, the researcher obtained the improvement of students, who achieved the Minimum Competence Criterion (70). There were 14 (53%) students who got score among 85-100 classified as “Very Good Criteria”, 12 (42%) students got score among 75-84 classified as “Good Criteria”. Based on the result above the researcher concludes that How Special Am I Game could be done in teaching vocabulary and increasing the students’ ability in mastering vocabulary.